Identifying the Mindset of Elementary School Children Using Learning Application : Kebersihan - Muhammad Firmansyah Suprapto; Sumenge T.G. Kaunang; Virginia Tulenan (Universitas Sam Ratulangi, 2021)
Abstract — Keeping the environment clean is an important thing in life. With a clean environment, a healthy life is created. But there are also some people who are less aware of protecting the environment. World education has taught to know more about the environment and what impact it will have if students do not care about the environment. This study aims to design and build interactive learning applications that can convey interesting and fun learning about how to keep the surrounding environment clean using the Multimedia Development Life Cycle method. From the results of the research evaluation, it can introduce learning methods using learning applications and assess changes in the mindset of students.Abstrak — Menjaga kebersihan lingkungan merupakan halyang penting dalam kehidupan. Dengan adanya lingkungan yangbersih maka akan tercipta kehidupan yang sehat. Namun ada juga beberapa orang yang kurang menyadari akan pentingnya menjaga lingkungan. Dalam dunia pendidikan telah diajarkan untuk lebih mengenal tentang lingkungan serta dampak apa yang ditimbulkan jika siswa tidak peduli dengan lingkungan sekitar. Penelitian ini bertujuan untuk merancang dan membangun aplikasi pembelajaran interaktif yang dapat menyampaikan pembelajaran secara menarik dan menyenangkan tentang cara menjaga kebersihan lingkungan sekitar menggunakan metode Multimedia Development Life Cycle. Dari hasil evaluasi penelitian dapat memperkenalkan metode pembelajaran menggunakan aplikasi pembelajaran serta menilai perubahan pola pikir dari siswa. Kata kunci — Aplikasi; Edukasi; Kebersihan; Multimedia.